Clinical Significance and Pathogenic Mechanisms of Long Non-Coding RNA TRPM2-AS in Cancers - Shichen Huang MS; Bowen Li MS; Huanyu Chen MD; Cheng Rong; Zheng Yang MD; Xianqin Zhang PhD (Technology in Cancer Research & Treatment)
Long non-coding RNAs (lncRNAs) are known to play vital roles in human cancers. LncRNA TRPM2-AS has been found to be upregulated in various types of cancers. The elevated levels of TRPM2-AS are associated with important clinicopathological parameters such as tumor size, tumor stage, and lymph node metastasis, revealing that TRPM2-AS could be a potential target for cancer diagnosis, prognosis and treatment. Moreover, TRPM2-AS is involved in regulating the cell proliferation, migration, invasion, apoptosis, drug or radio resistance by serving as a competing endogenous RNA, directly bounding to proteins and regulating multiple signaling pathways. In this review, we comprehensively summarize the latest knowledge on the aberrant expression of TRPM2-AS, the relationship between TRPM2-AS and clinical features, and the detailed mechanisms of potential functions of TRPM2-AS in various cancer types. The current study highlights the potential of TRPM2-AS as a prognostic and therapeutic target in cancers.